Randomized Trial of Weekly, Twice-Monthly, and Monthly Interpersonal Psychotherapy as Maintenance Treatment for Women With Recurrent Depression - Frank, Ellen (2007)
OBJECTIVE: The authors sought to determine whether a greater frequency of interpersonal psychotherapy (IPT) sessions during maintenance treatment has a greater prophylactic effect than a previously validated once-a-month treatment. METHOD: A total of 233 women 20–60 years of age with recurrent unipolar depression were treated in an outpatient research clinic. After participants had achieved remission with weekly IPT or, if required, with weekly IPT plus antidepressant pharmacotherapy, they were randomly assigned to weekly, twice-monthly, or monthly maintenance IPT monotherapy for 2 years or until a recurrence of their depression occurred. RESULTS: Among participants who remitted with IPT alone and entered maintenance treatment (N=99), 19 (26%) of the 74 who remained in the study throughout the 2-year maintenance phase experienced a recurrence of depression. Among participants who required the addition of a selective serotonin reuptake inhibitor to achieve remission (N=90), 32 (36%) sustained that remission through continuation treatment and drug discontinuation and began maintenance treatment; of these, 13 (50%) of the 26 who remained in the study throughout the maintenance phase experienced a recurrence. Survival analysis of time to recurrence by randomized treatment frequency showed no effect on recurrence-free survival in either treatment subgroup. CONCLUSIONS: These results suggest that maintenance IPT, even at a frequency of only one visit per month, is a good method of prophylaxis for women who can achieve remission with IPT alone. In contrast, among those who require the addition of pharmacotherapy, IPT monotherapy represents a significantly less efficacious approach to maintenance treatment.